Tailored fragments of roseophilin selectively antagonize Mcl-1 in vitro. Issue 23 (3rd June 2015) - Bracken, Jack D.; Carlson, Andrew D.; Frederich, James H.; Nguyen, Mai; Shore, Gordon C.; Harran, Patrick G.
Graphical abstract: Abstract: We have discovered a fragment of the natural product roseophilin, a member of the prodiginine family, that antagonizes Mcl-1 functions in a liposome-based assay for mitochondrial membrane permeabilization. By tailoring this substance such that it can participate in salt bridging with the protein surface, we have prepared the first prodiginine inspired structure that shows direct, saturable binding to a recombinant Bcl-2 family member in vitro.